Un projet partagé au service des acteurs : la plateforme d’Observatoires photographiques du paysage en Bretagne (POPP-Breizh) - Laurence Le Dû-Blayo; Caroline Guittet (Projets de Paysage)
For the most part, Photographic Observatories of the Landscape are confronted with limiting factors when it comes to facilitating the sharing of documents, the sustainability of archiving and the reliability of metadata as well as the capacity to use it. The realisation of these limiting factors by the organisations supporting the Observatories in Brittany led us to propose a project for a platform within a research programme funded by the regional council of Brittany. This POPP-Breizh project for a platform for Photographic Observatories of the Landscape in Brittany was validated in June 2011 by the regional landscape committee and was implemented thanks to the funding of a thesis grant via a regional environmental and urban planning agency co-funding programme involving the regional council and the European Regional Development Fund for the IT development of the platform. This platform project, providing support services (putting photographic series online, indexing metadata, and circulating documents among stakeholders and the public), soon produced positive results well beyond the initial scope of the project, especially regarding two aspects : the building of a network of stakeholders and the sharing of innovations. As a result, it is also in the co-construction of the collaborative management of the programme’s implementation that POPP-Breizh has proved to be an innovative and complex project.